Influences of Substrate Grain Size on the Burrowing Behavior of Juvenile Meretrix meretrix - Changsheng Zhang; Suyan Xue; Jiaqi Li; Jinghui Fang; Lulei Liu; Zhanfei Ma; Wenhan Yu; Haonan Zhuang; Yuze Mao (Animals, 2022)
The substrate is the key environmental factor that affects the growth, survival, population and distribution of dwelling mollusks in mudflat settings. To clarify the effect of the substrate grain size on soft substrate preference, burrowing ability and behavior during the selection process of juvenile Meretrix meretrix, four different grain size substrates (coarse sand, medium sand, fine sand, and natural substrate) were set up for comparison. The results indicated that: (1) the burrowing ability of juvenile specimens in fine sand was the strongest; (2) the degree (from high to low) of the juvenile’s preference for the four substrates was in the order of fine sand > natural substrate > medium sand > coarse sand; and (3) the selection process of the substrate by the juveniles could be divided into four stages: preparation, selection, burrowing and end stages. These stages showed the behavioral characteristics of a longer selection time and higher percentage of movement in coarse sand. Therefore, our results demonstrated that sea areas or ponds with fine sand as the main component are more suitable for stock enhancement with M. meretrix. These results provide basic data for habitat selection and suitability evaluations for the aquaculture of M. meretrix.